An insight into Malay medical manuscript MSS 4016 and typhoid rever remedies - Mohd Shafri, Mohd Affendi; Ahmad Nadzirin, Izzuddin; Ruzaidee, Ahmad Hakimi; Ismail, Mohamad Adib (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia, 2021)
Records of traditional Malay medicine to treat various diseases, including typhoid fever, are contained in handwritten manuscripts. Typhoid, known in Malay as kepialu, is a bacterial infection caused by Salmonella enterica serovar Typhi (S. Typhi). The infection could be treated in the past using chloramphenicol, however chloramphenicol-resistant strain has emerged necessitating effort to find new drug candidates against typhoid fever. This study aims to extract and analyse the content of a Malay medical manuscript MSS 4016 pertaining to typhoid fever. The manuscript was first transliterated from Jawi to Roman alphabets using standard philological system. The formulations for typhoid fever were extracted and numbered. The ingredients were listed respective to each number. Then, comparative analysis against modern research was performed using Google Scholar journal database employing specific keywords such as the scientific names of plants and typhoid fever, combined using Boolean Operators, in any time frame. From 66 diseases and 248 differing formulations contained in the manuscript, 16 formulations were intended for typhoid fever involving the use of 63 types of plants. From the comparative analysis, 50 were reported in contemporary modern publications as having various pharmacological activities related to typhoid. Thirty-four plants possess antibacterial property and specifically 18 plants have been shown to inhibit the growth of S. Typhi such as Allium cepa, Allium sativum and Nigella sativa. MSS 4016 is indeed an ancient pharmacopoeia holding a lot of medicinal information on numerous diseases. The valuable information gathered from this study may preserve knowledge in the manuscript while at the same time help in discovering potential plants for typhoid treatments.